2018
DOI: 10.1002/aic.16436
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐induced polar/nonpolar mixture separation performance in a film evaporation process

Abstract: Selective microwave heating and irradiation reportedly have a significant impact on the relative volatility of polar/nonpolar mixtures. However, the use of this feature for a separation process has not yet been reported. In this article, a microwave‐induced film evaporation process based on a nonequilibrium process was developed to separate polar/nonpolar mixtures. The influencing mechanism of microwaves on the separation of a polar/nonpolar system was studied by comparing the experimental results in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…There is an emerging interest in deploying microwave technology (MWT) for energy efficient, rapid, volumetric, and selective heating. The potential of using renewable solar and wind energy to power microwave (MW) devices makes the technology even more appealing. MW heating is primarily driven by dipole polarization and ionic conduction inside the heated materials and directly deposits energy volumetrically, instead of relying on conventional conduction and convection.…”
Section: Introductionmentioning
confidence: 99%
“…There is an emerging interest in deploying microwave technology (MWT) for energy efficient, rapid, volumetric, and selective heating. The potential of using renewable solar and wind energy to power microwave (MW) devices makes the technology even more appealing. MW heating is primarily driven by dipole polarization and ionic conduction inside the heated materials and directly deposits energy volumetrically, instead of relying on conventional conduction and convection.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 47 designed a microwave‐induced film evaporator for the separation of polar/non‐polar azeotropic mixture, and studied the influence mechanism of microwave on the separation of polar/non‐polar system. It is found that microwave irradiation can increase the vaporization of polar substances, and appropriate increase of microwave power can improve the separation effect.…”
Section: Experimental Study and Mechanism Analysis Of Microwave‐assis...mentioning
confidence: 99%
“…Water treatment and water reuse techniques, including water softening, brackish water purification, , and wastewater treatment, , are important to relieve water resource crisis. Various methods have been applied in water treatment, such as evaporation, distillation, and adsorption . Membrane-based separation process is one of the most crucial technologies for water treatment because of the high efficiency, easy operation, and relatively low energy consumption .…”
Section: Introductionmentioning
confidence: 99%